Least Change Secant Update Methods for Nonlinear Complementarity Problem (2014)
In this work, we introduce a family of Least Change Secant Update Methods for solving Nonlinear Complementarity Problems based on its reformulation as a nonsmooth system using the one-parametric class of nonlinear complementarity functions introduced by Kanzow and Kleinmichel -- We prove local and superlinear convergence for the algorithms -- Some numerical experiments show a good performance of this algorithm